Polyhydroxyalkanoate (PHA) synthesis by newly bacterial isolates using non-detoxified rice husk hydrolysate - Tanamool, Varavut; Soemphol, Wichai (Asia-Pacific Journal of Science and Technology, 2016)
Rice husk, a low cost carbon sources from agricultural waste was used for PHAs production. However, the structural complexity of lignocellulosic materials in rice husk requires a pretreatment step prior used as carbon source. The effect of the main operating factors including sulfuric acid concentration and hydrolysis temperature on fermentable sugar production from rice husk were investigated by response surface methodology. The results indicated that total sugar and reducing sugar concentration ranged between 12.36 and 30.12 g/L, and 0.28 and 6.66 g/L, respectively. The satisfactory condition of 9.20 % w/v sulfuric acid at 107.86 0C was established for reducing sugar and total sugar productions. Furthermore, the non-detoxified rice husk hydrolysate was then used as a carbon source for 10 isolate microbial strains to test PHA production capability. It was found that the highest biomass was observed as 1.01g/l and PHA content as 11.2 %.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">